Exosomal microRNA panel as a diagnostic biomarker in patients with hepatocellular carcinoma - Yang, Jingwen; Dong, Weiwei; Zhang, He; Zhao, Huixia; Zeng, Zhiyan; Zhang, Fengyun; Li, Qiuwen; Duan, Xiaohong; Hu, Yanyan; Xiao, Wenhua (Frontiers in Cell and Developmental Biology, 2022)
Background: Diagnostic tools for hepatocellular carcinoma (HCC) are critical for patient treatment and prognosis. Thus, this study explored the diagnostic value of the exosomal microRNA panel for HCC. Methods: Expression profiles of microRNAs in exosomes and plasma of HCC and control groups were assessed using microRNA microarray analysis. Reverse transcription-quantitative PCR was applied to evaluate the expression of candidate microRNAs in blood samples from 50 HCC patients, 50 hepatic cirrhosis patients, and 50 healthy subjects. The area calculated the diagnostic accuracy of the microRNAs and microRNA panel under the receiver operating characteristic curve (AUC). Results: MicroRNA microarray analysis revealed that there were more differentially expressed microRNAs in the exosome HCC group than plasma HCC group. Among the 43 differentially expressed microRNAs contained in both exosomes and plasma, we finally decided to testify the expression and diagnostic significance of microRNA-26a, microRNA-29c, and microRNA-199a. The results indicated that expression of the microRNA-26a, microRNA-29c, and microRNA-199a in both exosomes and plasma was significantly lower in HCC patients compared with hepatic cirrhosis and healthy group. Interestingly, exosomal microRNAs were substantially more accurate in diagnosing HCC than microRNAs and alpha-fetoprotein in plasma. Moreover, the exosomal microRNA panel containing microRNA-26a, microRNA-29c, and microRNA-199a showed high accuracy in discriminating HCC from healthy (AUC = 0.994; sensitivity 100%; specificity 96%) and hepatic cirrhosis group (AUC = 0.965; sensitivity 92%; specificity 90%). Conclusion: This study revealed that the exosomal microRNA panel has high accuracy in diagnosing HCC and has important clinical significance.